RETRACTED: Yang et al. Capacitive Behavior of Aqueous Electrical Double Layer Based on Dipole Dimer Water Model. Nanomaterials 2023, 13, 16 - Songming Yang; Youer Deng; Shiqi Zhou (Nanomaterials)
The journal retracts the article titled “Capacitive Behavior of Aqueous Electrical Double Layer Based on Dipole Dimer Water Model” [...]